Analisis Pengaruh Motivasi, Kompensasi Dan Iklim Organisasi Terhadap Kepuasan Kerja Kepala Sekolah SD se-Kabupaten Bireuen - Iskandar, Iskandar; Yusuf, M. (Aceh Cooperative Care, 2022)
The study was conducted at public elementary schools (SD) throughout Bireuen Regency, with the sample aiming to analyze the effect of work motivation, compensation and school organizational climate on job satisfaction. Descriptive analysis and verification with path analysis approach. The results of the study found that all the factors included in the analysis model had a direct and indirect effect on the objective factor, namely job satisfaction. Each calculation results are; (1) the effect of motivation is 26.37%. (2) the influence of the compensation aspect is 26.2% and the influence of organizational climate is 25.92%. (4) Simultaneously the factors of motivation, compensation and organizational climate have a significant contribution to the job satisfaction of elementary school principals in Bireuen Regency by 26.7%.